2017
DOI: 10.1093/bjsw/bcx018
|View full text |Cite
|
Sign up to set email alerts
|

‘Siblings as Better Together’: Social Worker Decision Making in Cases Involving Sibling Sexual Behaviour

Abstract: Sibling abuse is arguably the most prevalent form of family violence (Meyers, 2014), with sibling sexual abuse more common than parental sexual abuse (Krienert and Walsh, 2011). However, research on social worker decision making has been limited to situations concerning parental abuse, with almost no attention paid to situations where a child in the family presents a risk. This grounded theory study analyses from interviews with 21 social workers in Scotland their retrospective accounts of decisions relating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This research aimed to explore social workers' thinking processes behind the decisions they were involved in making following sibling sexual behavior becoming known. From rigorous grounded theory analysis of the social workers' accounts, Yates (2018) found that under conditions of uncertainty, social workers make largely intuitive decisions, influenced by their relationships with children and families, (Yates, 2018, p.181) This current paper continues to report from this original study by expanding and adding depth to the particular findings related to the underlying perspective of Sibling relationships as non-abusive and of intrinsic value.…”
Section: Social Worker Responses To Sibling Abusementioning
confidence: 84%
See 2 more Smart Citations
“…This research aimed to explore social workers' thinking processes behind the decisions they were involved in making following sibling sexual behavior becoming known. From rigorous grounded theory analysis of the social workers' accounts, Yates (2018) found that under conditions of uncertainty, social workers make largely intuitive decisions, influenced by their relationships with children and families, (Yates, 2018, p.181) This current paper continues to report from this original study by expanding and adding depth to the particular findings related to the underlying perspective of Sibling relationships as non-abusive and of intrinsic value.…”
Section: Social Worker Responses To Sibling Abusementioning
confidence: 84%
“…As reported in Yates (2018), the perspective was maintained by social workers sometimes doubting whether any sibling sexual behavior had indeed taken place. Where it was believed that it had occurred there was often a resistance to labelling the sexual behavior as abusive.…”
Section: Doubting What Happened and Resisting Labelling The Behavior mentioning
confidence: 95%
See 1 more Smart Citation
“…In Yates’ () doctoral research exploring social workers’ retrospective accounts of their decision making in cases involving sexual behaviour between siblings, analysis of these accounts found that social workers framed sibling relationships as non‐abusive and of intrinsic value. It was not within the social workers’ underlying perspective of sibling relationships to consider their providing a possible context in which abuse could take place.…”
Section: Discussionmentioning
confidence: 99%
“…PAPSA is an understudied phenomenon; however, recent studies have pointed to an increasing number of contexts in which preadolescents are involved as victims and offenders, for example, in cases of sibling sexual abuse (SSA; e.g., Tener, Tarshish, & Turgeman, 2017; Yates, 2018). It is important to state that the current literature review was designed in order to focus on PAPSA that takes place outside the family context in order to explore the way young and preadolescent children are exposed to PSA in other life contexts.…”
Section: The Current Literature Reviewmentioning
confidence: 99%